PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN KLINIK GIGI MMC - Fajar Pitaloka; Husnul Huluki (Jurnal Gici Jurnal Keuangan dan Bisnis, 2021)
The development of the world in the world of health is currently increasing rapidly, so that companies in managing their businesses are expected to be able to use human resources properly. Human resources are an important part of achieving organizational goals, both large and small companies. Given the increasingly intense competition between these companies, it requires companies to be able to survive and compete with other companies. The purpose of this study was to determine and analyze the Effect of Compensation and Work Environment on Employee Performance of MMC Dental Clinic. This type of research is explanatory research with the research method of collecting data using a questionnaire. The data analysis model used is multiple linear regression analysis.This study used nonprabobility sampling, while the sampling method used was saturated sampling. The sample consisted of 35 respondents, using multiple linear regression analysis. The regression test results show that 38% of employee performance factors can be explained by Compensation and Work Environment, and 72% are explained by other factors not examined in this study, while the F test results show that simultaneously the Compensation and Work Environment variables simultaneously affect positive and significant towards Employee Performance with the results of the analysis, namely F count (10.028)> F table (3.28). The results of the t test show that the work environment variable shows the results of the tcount analysis (2.072), so partially this variable does not have a positive and significant effect on the employee performance of MMC Dental Clinic. As for the compensation variable with the result of tcount analysis (2.513), this variable does not have a positive and significant effect on the employee performance of MMC Dental Clinic. Both variables do not affect the performance of MMC Dental Clinic Employees.